Tennis anatomy - Roetert, Paul; Kovacs, Mark (Human Kinetics, 2011)
This book has features the most-effective exercises for tennis players, with clear, step-by-step descriptions and full-color anatomical illustrations highlighting the muscles in action. You'll see how to strengthen muscles, reduce injury, and you'll learn how each exercise is fundamentally linked to tennis performance